Clinical characteristics associated with somatic GNAS mutations in acromegaly: a systematic review and institutional experience - Dillon, Brendan R.; Ruddy, Margaret; McQuade, Emily C.; Shah, Shruti N.; Twi-Yeboah, Alberta; Levinson, Benjamin A.; Agrawal, Nidhi (Frontiers in Endocrinology, 2026)
IntroductionAcromegaly is a rare, insidious disease associated with significant morbidity and mortality usually caused by a growth hormone (GH)-secreting pituitary tumor. Somatic mutations in GNAS are common in these tumors, yet their diagnostic, prognostic, and therapeutic implications are less clear.MethodsWe conducted a structured review of the literature and meta-analysis to investigate the association of GNAS mutation status with clinical characteristics and treatment outcomes in adult patients with acromegaly. This was complemented by an analysis comparing patients with acromegaly and identified tumor somatic GNAS mutations versus those without at our affiliated institution, NYU Langone Health.ResultsWe identified 55 publications that met our inclusion criteria, all observational in nature and most retrospective in design. Twenty-two patients with acromegaly at our institution underwent pituitary tumor resection followed by tumor somatic mutation analysis from 2022 to 2024. The aggregate prevalence of somatic GNAS mutations in acromegaly was 38% in the systematic review, which was similar to the prevalence of 41% at our institution. While some studies in our review found patients with GNAS mutated tumors were older and more frequently male, most did not find this association. Whether these tumors demonstrate greater GH secretory capacity is unclear. There was greater consistency in findings that GNAS+ tumors are smaller and possibly less invasive. While greater GH suppression to acute octreotide treatment was frequently reported in patients with GNAS+ tumors, most studies that investigated the response to long-term somatostatin receptor ligand (SRL) therapy did not find an association between GNAS mutation presence and biochemical control. At our institution, patients with GNAS+ tumors were older at the time of surgery and most classified as mammosomatotroph adenomas on pathology.ConclusionsDespite their high prevalence, GNAS mutations cannot reliably inform prognosis and treatment in acromegaly based on findings to date. Larger and prospective studies are needed exploring the frequency and intensity of preoperative symptoms and comorbidities, postoperative outcomes, and occurrence of prolactin co-secretion in GNAS+ tumors.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251107763.